Assessment of myeloperoxidase (Mpo) gene polymorphism in cervical cancer - Adalı, Yasemen; Pehlivan, Sacide; Oğuzkan Balcı, Sibel; Koyuncuoğlu, Meral (Journal of Surgery and Medicine, 2022)
Background/Aim: Cervical cancer (CC) is the most common gynecological malignancy in women. In spite of a variety of treatment protocols, it is necessary to carefully investigate all factors that play a role in the pathogenesis of these tumors which may have mortal progression. In this context, in our study we aimed to assess the myeloperoxidase (MPO) gene polymorphism, an important inflammatory enzyme, among cervix cancer cases. Methods: In this cross-sectional study, 79 cases diagnosed as cervical carcinoma between 1992-2012 is included. The cases without archival paraffin blocks and clinical follow-ups are excluded. All slides with tumor involvement are reviewed and the ones which demonstrate tumor’s characteristics are determined. After block determination 3 sections with 10-micron thickness obtained from paraffin blocks and MPO gene polymorphism was shown using acil restriction endonuclease enzyme with the restriction fragment length polymorphism (RFLP) method after polymerase chain reaction (PCR). The histopathological parameters including tumor stage and type, lymph node metastasis, ovary and endometrium involvement, recurrence and late metastasis are compared with genotype using chi-square and Fisher’s exact test. Results: The mean age of cases was 51.3 (10.9) years. Of 79 cases, 29 (36.7%) had AG (adenine-guanine) and 50 (633%) had GG (guanine-guanine) genotypes. Only endometrium involvement was identified to have a statistically difference with MPO gene polymorphism among the assessed histopathologic parameters (P=0.015). When clinical parameters are assessed, there was no difference identified between genotype and mortality (P=0.622). Conclusion: Cervical cancer is thought to have progressive and regressive characteristics of tumor development due to the inflammatory response of the host. Within this framework, in our study assessing gene polymorphism of one of the inflammatory response foundation stones of MPO, we identified more endometrial involvement for cases with AG genotype. We believe this significance will be encountered for more parameters in broad case series.